2018
DOI: 10.3389/fimmu.2018.01954
|View full text |Cite
|
Sign up to set email alerts
|

ATF3 Stimulates IL-17A by Regulating Intracellular Ca2+/ROS-Dependent IL-1β Activation During Streptococcus pneumoniae Infection

Abstract: Activating transcription factor-3 (ATF3) in the ER stress pathway induces cytokine production and promotes survival during gram-positive bacterial infection. IL-17A is a critical cytokine that is essential for clearance of Streptococcus pneumoniae. However, the mechanism by which ATF3 induces IL-17A production remains unknown. Here, we show that ATF3 induces IL-17A production via NLRP3 inflammasome-dependent IL-1β secretion. Survival rates were comparable in IL-17A-depleted and ATF3 KO mice but were lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Lee et al found that ATF3 −/− mice show decreased survival and bacterial clearance following S. pneumoniae infection. Macrophage ATF3 stimulates IL-17A production in lung γδ T cells to prompt host protection rapidly from early S. pneumoniae infection ( 54 ). Kim et al had found that oral treatment of metformin to either mouse with LPS-induced endotoxemia or ob/ob mice decreases the plasma and tissue levels of TNFα and IL-6 and upregulates ATF3 expression in spleen and lungs.…”
Section: Role Of Atf3 In Immunitymentioning
confidence: 99%
“…Lee et al found that ATF3 −/− mice show decreased survival and bacterial clearance following S. pneumoniae infection. Macrophage ATF3 stimulates IL-17A production in lung γδ T cells to prompt host protection rapidly from early S. pneumoniae infection ( 54 ). Kim et al had found that oral treatment of metformin to either mouse with LPS-induced endotoxemia or ob/ob mice decreases the plasma and tissue levels of TNFα and IL-6 and upregulates ATF3 expression in spleen and lungs.…”
Section: Role Of Atf3 In Immunitymentioning
confidence: 99%
“…In addition to the point IL-17A activated ER stress under some pathological conditions, there were also reports indicated ER stress, as a critical proinflammation factor, promoted the secretion of IL-17A [ 11 , 30 , 37 ]. Therefore, we explored the effects of ER stress on IL-17A production in macrophage both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, ATF3, as a key transcription factor in ER stress, positively regulated IL-17A production. After infected with S.pneumoniae, ATF3 KO mice showed a marked reduction of IL-17A expression in lung compared to that in WT mice [ 37 ]. Also, T lymphocytes and peripheral blood mononuclear cells responded to ERS by activating the IRE1/XBP1 signaling pathway, promoting secretions of IFN-γ, IL-17A, and IL-2 in a study about ulcerative colitis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here are consistent with our previous study demonstrating significantly elevated cytoplasmic Ca 2+ by S. uberis infection (14). This is associated with the activation of PLC and hydrolyzation PIP2 to produce IP3 which bonds to Ca 2+ channels allowing Ca 2+ entry (41, 42). We found that the expression and activation of PLCγ1 the main isoform of PLC in epithelial cells (43) and cytoplasmic IP3 increases after S. uberis challenge.…”
Section: Discussionmentioning
confidence: 99%